Zero-waste: a new sustainability paradigm for addressing global waste problem - Zaman, Atiq (Springer, 2022)
There is a growing interest in addressing global waste problems by applying innovative ideas and philosophies such as zero-waste and circular economy. As a new sustainability paradigm, zero-waste challenges the common assumption of waste as a valueless and unavoidable by-product created at the end of the product’s life phase. Instead, it acknowledges that waste is a “misallocated resource” or “resource in transition”; produced during the intermediate phases of production and consumption activities. Waste should be recirculated to production and consumption processes. Therefore, zero waste means no “waste” would be wasted under the circular economy system. This chapter presents various examples of zero-waste practices derived from family, community, business, and city levels. In addition, zero-waste implementation strategies and actions are also discussed in the chapter. Despite its potential, the visionary zero-waste goals cannot be achieved without responsible global stewardship and active citizens’ role.